If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -3 + (x + -1) = 12 Reorder the terms: 15 + -3 + (-1 + x) = 12 Remove parenthesis around (-1 + x) 15 + -3 + -1 + x = 12 Combine like terms: 15 + -3 = 12 12 + -1 + x = 12 Combine like terms: 12 + -1 = 11 11 + x = 12 Solving 11 + x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + x = 12 + -11 Combine like terms: 11 + -11 = 0 0 + x = 12 + -11 x = 12 + -11 Combine like terms: 12 + -11 = 1 x = 1 Simplifying x = 1
| 4y+5y=9 | | n+84=50 | | (10+x)(3x-11)=0 | | (x+5y)2= | | 1/5x=1/9x | | 4y+3=3y+8-2.33 | | -4x+15=31 | | (4x-2)(x+2)=15x+5 | | 9+2n=39 | | 9a=-18 | | 8x(6)=128 | | -4x+1531= | | (3x+12)=18 | | 12x+6=14x-6 | | 3z=81*2 | | (x-6/7)+6/7=-x/5 | | 5x+6-3x= | | 2x^2-5x+15=0 | | 3z=81 | | 180=y+5+3y-1 | | [r+1]=2 | | 17+X-11=3X | | 1n-8=2 | | 180=4x-2+x+10 | | -5(y-3)=25 | | 3x/8+3x/4=9 | | (X-4)=6 | | [x+2][x+5]= | | 4q=6 | | -2x+59= | | -7x+4+8x=4 | | 12.5=5v |